Moran’s I and Geary’s C: investigation of the effects of spatial weight matrices for assessing the distribution of infectious diseases - Sarah Isnan; Ahmad Fikri bin Abdullah; Abdul Rashid Shariff; Iskandar Ishak; Sharifah Norkhadijah Syed Ismail; Maheshwara Rao Appanan (Geospatial Health)
The COVID-19 outbreak has precipitated severe occurrences on a global scale. Hence, spatial analysis is crucial in determining the relationships and patterns of geospatial data. Moran’s I and Geary’s C are prominent methodologies used to measure the spatial autocorrelation of geographical data. Both measure the degree of similarity or dissimilarity between nearby locations based on attribute values in such a way that the selection of distance techniques and weight matrices significantly impact the spatial autocorrelation results. This paper aimed at carrying out the spatial epidemiological characteristics analysis of the pandemic comparing the results of Moran’s I and Geary’s C with different parameters to gain a comprehensive understanding of the spatial relationship of COVID-19 cases. We employed distance-based techniques, K-nearest neighbour, and Queen contiguity techniques to assess the sensitivity of the different parameter configurations for both Moran’s I and Geary’s C. The findings revealed that former provided more reliable and robust results compared to the latter, with consistent results of spatial autocorrelation (positive spatial autocorrelation). The distance weight of 0.05 using the Manhattan method of Moran’s I is the recommended distance weight, as it outperformed other weight matrices (Moran’s I = 0.0152, Z-value= 110.8844 and p-value=0.001).